The Modelling of Stock Price Based on Dividend Policy, Intellectual Capital, Sales Growth, and Capital Structure - Kenny Ardillah; Icha Juana (Jurnal Ilmu Manajemen dan Ekonomika, 2021)
This research was aimed to know the influences of dividend policy, intellectual capital, sales growth and capital structure on stock prices. The population in this study were all mining companies listed on the Indo-nesia Stock Exchange in 2015 – 2019. The number of research samples obtained was 38 companies with purposive sampling technique and the number of observations of research data obtained was 190. This study used the multiple linear regression method with a fixed effects approach model. The results show that dividend policy has no influence on stock prices, intellectual capital has no influence on stock prices, sales growth has no influence on stock prices, and capital structure has a negative and significant effect on stock prices. The results of this study can provide insight to the companies, so that it can more effectively manage its capital structure.